Effect of Enterococcus faecium as a Water and/or Feed Additive on the Gut Microbiota, Hematologic and Immunological Parameters, and Resistance Against Francisellosis and Streptococcosis in Nile Tilapia (Oreochromis niloticus) - Suphoronski, Suelen Aparecida; de Souza, Felipe Pinheiro; Chideroli, Roberta Torres; Mantovani Favero, Leonardo; Ferrari, Natália Amoroso; Ziemniczak, Henrique Momo; Gonçalves, Daniela Dib; Lopera Barrero, Nelson Mauricio; Pereira, Ulisses de Padua (Frontiers in Microbiology, 2021)
In the present study, we evaluated the effects of administering Enterococcus faecium in food and/or water on the hematological and immunological parameters, intestinal microbiota, resistance to bacterial diseases (streptococcosis and francisellosis) and growth of Nile tilapia. Before the in vivo experiment, probiotic bacteria isolated from Nile tilapia were selected via inhibition tests. Sequencing, annotation, and assembly of the complete genome of the selected bacteria as well as other tests were performed using bioinformatics tools. Three treatments were implemented: G1 (probiotic feeding), G2 (probiotic in water), and G3 (probiotic in food and water); and a negative control (NC) was also employed. Treatment lasted 38 days, and each group consisted of fish and 2 repetitions. The fish were divided and infected with Streptococcus agalactiae S13 (serotype Ib) and Francisella orientalis. The G1 group had a higher average final weight gain than the G2, G3, and NC groups. Further, a significant increase in the number of thrombocytes was observed in the groups administered probiotics in the diet (G1 and G3). A statistical difference was observed in the mortality of fish infected with S. agalactiae in the NC compared to the treated groups. Cetobacterium was the 43 most abundant genus in the intestinal microbiota of all groups, including the NC group. Enterococcus faecium increased the immunity of fish administered the treatment and decreased the mortality caused by S. agalactiae. As an autochtone probiotic, Enterococcus faecium does not interfere with the local ecosystem and thus has a great probiotic potential for Nile tilapia in Brazil.